Easyhighlite Accounting - Tan, Angeline; Francis, Daniel Jason; Abdul Shukur, Noor Dasreena Shukria (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
‘EasyHighlite Accounting’ is a technique using colour-coding with highlighter pens in the preparation of accounts related to changes in business structure under MFRS 3. This technique was innovated to enhance lecturers' teaching and learning practices and will improve students' proficiency and comprehension of preparing of accounts related to changes in business structure. 75% respondents stated there are too many items in the additional information and 54.2% respondents stated they are confused about which item belongs to sellers and which belongs to buyer. EasyHighlite Accounting uses a highlighter pen with colour code, and students have to colour each item in the additional information using three different highlighter pens. Each highlighter pen represents one entity, either sellers, buyer or both entities. This technique is to make it easier for students to see the colour directly in preparing the accounts related to changes in business structure. The sample of this study consists of 24 Diploma of Accountancy students (Semester 5) Department of Commerce, Politeknik Kuching Sarawak. The result for Quiz 2 for Session I 2024/2025 increased by 23.5%. EasyHighlite Accounting incorporates a visual learning strategy using colour-coding with highlighter pens. This technique is unique as it uses three different colours to visually distinguish which information belongs to the seller, the buyer, and both entities. This technique will benefit the students and the lecturers to enhance the learning process in preparing the accounts related to changes in business structure under MFRS 3. The commercial potential of EasyHighlite Accounting could be packaged with custom-designed colour-coded highlighter pens and instructional guides to engage the students using the same colour and make the learning process more interesting. In conclusion, EasyHighlite Accounting represents a breakthrough in accounting education, offering a simple yet effective solution to the accounting students for diploma level.